Computational Modeling of Fluid–Structure–Acoustics Interaction during Voice Production - Jiang, Weili; Zheng, Xudong; Xue, Qian (Frontiers in Bioengineering and Biotechnology, 2017)
The paper presented a three-dimensional, first-principle based fluid-structure-acoustics interaction computer model of voice production which employed a more realistic human laryngeal and vocal tract geometries. Self-sustained vibrations, important convergent-divergent vibration pattern of the vocal folds and entrainment of the two dominant vibratory modes were captured. Voice-quality associated parameters including the frequency, open quotient, skewness quotient, and flow rate of the glottal flow waveform were found to be well within the normal physiological ranges. The analogy between the vocal tract and a quarter-wave resonator was demonstrated. The acoustic perturbed flux and pressure inside the glottis were found to be at the same order with their incompressible counterparts, suggesting strong source-filter interactions during voice production. Such high fidelity computational model will be useful for investigating a variety of pathological conditions that involve complex vibrations, such as vocal fold paralysis, vocal nodules and vocal polyps. The model is also an important step toward a patient-specific surgical planning tool can serve as a no-risk trial and error platform for different procedures, such as injection of biomaterials and thyroplastic medialization.